Antibiotics resistance in clinical settings, emergence threat and control measurements: A review - Fatima Moeen Abbas (Alnakhla Journal of Science, 2026)
Antibiotics resistance (AR) has been regarded as a critical health issue threating the efficacy of antibiotics treatment and rising medical care costs. Management of multi-drug resistant (MDR) bacteria is difficult and represent a complex challenge to clinician resulting in significant mortality and morbidity. Misuse or improper utilization of antibiotics along with poor infection control practice in clinical settings is the major risk factors for emergence resistance in bacterial strains. This review investigate resistance to antibiotics in clinical facilities, identify risk factors and assess the most effective and newer solutions to combat resistance and prevent transmission of resistant pathogens to natural ecosystem. Phage therapy, monoclonal antibodies and nanoparticles are effective tools to overcoming antibiotics resistance challenges.